Students’ Speaking Anxiety in English Education Study Program - Wandi Syahfutra (ELT-Lectura, 2021)
This study explores speaking anxiety: the identification of speaking anxiety in English education study program. Using a mixed methods approach, this research selected two different categories, students studying in English Education Department private university and those studying in English Education Department in public university as research participants. The findings suggest that the main factors of speaking anxiety causes at public university were essentially affected by nervousness and idea delivery. Nevertheless, English students in private university claimed that their dominant cause is rooted from self-confidence; considering mistakes and lecturers’ attitude during English speaking performance. This research is beneficial in enriching literature in the scope of English education department, especially in Indonesia and others state adopting English as foreign language. It is crucial to note that students’ voice is worth to listen, as a reflection for English teachers or lecturers identifying their students’ speaking anxiety to apply appropriate and a more effective learning method.